An Archaeological Investigation Conducted at Okai Koi Hill (Ayawaso) and Its Significance for Iron Age archaeology in Ghana - Bredwa-Mensah, Y. (University of Ghana, 1990)
Archaeology in Ghana has a long and respectable tradition especially in relation to other areas in the West African sub-region. Despite this encouraging situation, significant gaps still exist in our understanding of the History of some early societies in Ghana. The need to apply an archaeological research strategy holistic in approach as a means of reconstructing a general and broad history of ancient Ghanaian societies, to fill in the gaps, cannot be over-emphasised. It is in this vein that this research on the Ga of the Greater Accra Region of Ghana was undertaken. The Ga,who occupy the western Accra Plains, founded early settlements some of which are in ruins, from the coast to a few kilometers inland. This research, focused on Ayawaso, the former capital of the Ga, which was referred to in early European written documents as Great Accra
MPhil.Theses
Keywords: Archaeology; Early Societies; Ancient; Ga; Ghana